The level of the pushiation among postgraduate students who working in the field of teaching in the light of some demographic variables - Ali, Sayed Ibrahim (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identify the level of pushiation among postgraduate students working in the field of teaching in Al-Ahsa Governorate in the light of some demographic variables in a sample of (49) male and female students at the postgraduate level at the College of Education and from those working in the field of teaching, at a rate of (23) Male students, (26) female students, with average age (32.22) and the study tools included the pushiation scale (Preparation / Gaber, 2021), and the descriptive approach was used. The results showed that the level of pushiation among postgraduate students working in the field of teaching was high. It also showed that there is a statistically significant difference between postgraduate students working in the field of teaching in the pushiation due to the gender variable in favor of females, and there is no statistically significant difference at the level of significance ≤ (0.05) among the postgraduate students working in the field of teaching in the pushiation due to the specialization variable And the absence of a statistically significant difference at the level of significance ≤ (0.05) between postgraduate students working in the field of teaching in the pushiation due to the variable of professional experience, and the presence of a statistically significant difference between the postgraduate students working in the field of teaching in the pushiation is attributed to the variable of educational level, and the absence of a statistically significant difference between postgraduate students working in the field of teaching in the pushiation due to the variable of social level, and the absence of a statistically significant difference between the postgraduate students working in the field of teaching in the pushiation due to the level variable in the economic variable. The study recommended focusing on imparting the concept of Pushiation to postgraduate students through workshops held for them by the Saudi Ministry of Education, and paying attention to including Pushiation skills, especially professional and academic Pushiation, in teacher preparation programs in faculties of education.